Direct contact is the way to go - Andrews, Phil (Daily mercury (Guelph. 1967), 2010)
Sort out how many folks you talk to some day. Even a reciprocated 'hello' to a passerby counts. But e-mail, Twitter messaging and vigorous Facebooking doesn't count. They didn't exist when [Jim MacNeil] crafted the rule and I'm betting he would come down in the direct human-to-human contact camp for 'official' contacts counted. At least I got out of the newsroom for a spell. I'm no longer a reporter but I've got to make sure I push myself to see and connect in person with subjects we're covering or might be. E-mail and other IT communication tools are great. They've changed the world and journalism too. But there's still a special value in having direct contact with other people. Lots of it-particularly in this line of work.